MODELLING ECONOMIC GROWTH IN GHANA - Mends, Edwin Brew; King, Avordeh Timothy; Forson, Daniel Yeboah (European Scientific Journal, ESJ, 2012)
The main aim of this paper was to use the Augmented Cobb-Douglas production function as a basis to model the economic growth of Ghana during the period 1991 to 2011. There has not been equality of economic growth around the world for a long time. In all economies around the, some grow faster than others. Economists have predicted after some few years to come that the slower growing economies will eventually converge to the faster growing economies. Starting from the estimates of the parameters from other studies, the growth model was simulated for the period 1991 to 2011, using Matlab, SPSS and Excel spreadsheet. The estimations from the model were compared with the actual figures from the Ghana Statistical Service, World Bank and Ministry of Finance and Economic Planning (MOFEP). The model in this paper provides a better approximation of the changes in the Ghanaian economy for the period from 1991 to 2011, with respect to the changes of the real aggregate in the Gross Domestic Product (GDP) growth and to the ratios of the main macroeconomic variables, like production per worker, capital-output ratio or capital per worker. The matlab simulation results showed a very close relationship between the actual and calculated growth rates over the periods. The actual average growth rate over the period was 4.5% as compared to the calculated average value of 4.21%. In conclusion, the correlation coefficient between the actual growth rates and the calculated was 0.298, which indicates that they are correlated, but the strength of correlation was weak meaning the model is good for prediction of any countries economic growth.